The role of vitamin D and VDR in carcinogenesis: Through epidemiology and basic sciences. Issue 167 (March 2017) - Bandera Merchan, Borja; Morcillo, Sonsoles; –>Martin-Nuñez, Gracia; Tinahones, Francisco José; Macías-González, Manuel
Abstract: In the last two decades vitamin D (VD) research has demonstrated new extraskeletal actions of this pre-hormone, suggesting a protective role of this secosteroid in the onset, progression and prognosis of several chronic noncommunicable diseases, such as cardiovascular disease, diabetes mellitus or cancer. Regarding carcinogenesis, both preclinical and epidemiological evidence available show oncoprotective actions of VD and its receptor, the VDR. However, in late neoplastic stages the VD system (VDS) seems to be less functional, which appears to be due to an epigenetic silencing of the system. In preclinical experimental studies, VD presents oncoprotective actions through modulation of inflammation, cell proliferation, cell differentiation, angiogenesis, invasive and metastatic potential, apoptosis, miRNA expression regulation and modulation of the Hedgehog signalling pathway. Moreover, epidemiological evidence points towards an oncoprotective role of vitamin D and VDR in colorectal cancer. This association is more controversial with breast, ovarian and prostate cancers, although with a few adverse effects. Nonetheless, we should consider other factors to determine the benefit of increased serum concentration of VD. Much of the epidemiological evidence is still inconclusive, and we will have to wait for new, better-designed ongoing RCTs and their results to discern the real effect of vitamin D in cancer risk reduction and therapy. The objective of this literature review is to offer an up-to-date analysis of the role of the VD and VDR, in the onset, progression and prognosis of all types of cancer. We further discuss the available literature and suggest new hypotheses and future challenges in the field of VD research.